PENGARUH COMPANY’S PROMOTIONAL ACTIVITIES, IMPROVEMENT OF WAITING ENVIRONMENT, QUEUING MANAGEMENT BY THE COMPANY TERHADAP CUSTOMER PERCEPTIONS REGARDING WAITING TIME PADA EVENT GARUDA TRAVEL FAIR SURABAYA - Prito Rino Pradito (Perpustakaan Universitas Surabaya, 2019)
Abstrak – Penelitian ini bertujuan untuk menguji pengaruh company’s promotional activities, improvement of waiting environment, queuing management by the company terhadap customer perceptions regarding waiting time pada event Garuda Travel Fair. Penelitian ini dilakukan dengan menggunakan Structural Equation Modelling dengan software SPSS 18.0 dan AMOS. Penelitian ini mengambil data sebanyak 150 responden yang pernah mengantri dalam event Garuda Travel Fair. Hasil penelitian ini menemukan bahwa company’s promotional activities berpengaruh positif terhadap customer perceptions regarding waiting time. Queuing management by the company berpengaruh positif terhadap customer perceptions regarding waiting time. Improvement of waiting environment berpengaruh positif terhadap customer perceptions regarding waiting time. Company’s promotional activities berpengaruh positif terhadap improvement of waiting environment. Queuing management by the company berpengaruh positif terhadap improvement of waiting environment Kata kunci: company’s promotional, waiting environment, queuing management, dan waiting time Abstract – The purpose of this study is to explore the effect company’s promotional activities, improvement of waiting environment, queuing management by the company terhadap customer perceptions regarding waiting time pada event Garuda Travel Fair. This study using Structural Equation Modelling with SPSS 18.0 and AMOS. This study took 150 respondents who ever queued in Garuda Travel Fair Surabaya event. The result of this study found that company’s promotional activities have a positive effect on customer perceptions regarding waiting time. Queuing management by the company has a positive effect on customer perceptions regarding waiting time. Improvement of waiting environment has a positive effect on customer perceptions regarding waiting time. Company’s promotional activities has positively affect the improvement of waiting environment. Queuing management by the company has a positive effect on the improvement of waiting environment Keywords : company’s promotional, waiting environment, queuing management, dan waiting time